2013
DOI: 10.1371/journal.pone.0070032
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine and Vitamin D Adjunctive Therapies in Pulmonary Tuberculosis: A Randomised, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundVitamin D (vitD) and L-arginine have important antimycobacterial effects in humans. Adjunctive therapy with these agents has the potential to improve outcomes in active tuberculosis (TB).MethodsIn a 4-arm randomised, double-blind, placebo-controlled factorial trial in adults with smear-positive pulmonary tuberculosis (PTB) in Timika, Indonesia, we tested the effect of oral adjunctive vitD 50,000 IU 4-weekly or matching placebo, and L-arginine 6.0 g daily or matching placebo, for 8 weeks, on proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 50 publications
7
106
2
3
Order By: Relevance
“…This study also did not observe any significant change in the above mentioned clinical score with vitamin D in PTB patients. 18 The similar non-significant findings were also reported by Salahuddin et al inTB score, with Vitamin D supplemented and placebo groups at 4 weeks (p-value 0.16), 8 weeks (p-value 0.89) and 12 weeks (p-value 0.16). 14 Farazi et al found an association between TB severity score with lower levels of serum calcidiol (p-value = 0.043) in Vitamin D (single dose of 450,000 IU) supplemented and placebo groups over 3 months.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study also did not observe any significant change in the above mentioned clinical score with vitamin D in PTB patients. 18 The similar non-significant findings were also reported by Salahuddin et al inTB score, with Vitamin D supplemented and placebo groups at 4 weeks (p-value 0.16), 8 weeks (p-value 0.89) and 12 weeks (p-value 0.16). 14 Farazi et al found an association between TB severity score with lower levels of serum calcidiol (p-value = 0.043) in Vitamin D (single dose of 450,000 IU) supplemented and placebo groups over 3 months.…”
Section: Discussionsupporting
confidence: 79%
“…15 A similar clinical outcome score was designed in a randomized, double-blind, placebo-controlled study conducted by Ralph et al (2013) where change in body weight, %FEV1 change, cough, sputum, hemoptysis was included. This study also did not observe any significant change in the above mentioned clinical score with vitamin D in PTB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Schö n et al (44) treated TB patients with oral L-arginine and observed subtle benefits, including increased sputum conversion and reduced cough and chest pain in HIV 2 patients. Yet a more recent study found no clinical benefit in supplementing L-arginine to M. tuberculosis-infected patients (45). The metabolic consequences of oral L-arginine supplementation may be responsible for these results.…”
Section: Discussionmentioning
confidence: 97%
“…Determinant of vitamin D status consists of; exposure to UVB radiation, clothing, nutrition, BMI, serum cholesterol, and genetic factors like skin pigmentation and enzymes in the metabolism of vitamin D [16]. Exposure to UV radiation is the most determinant factor [17].…”
Section: Resultsmentioning
confidence: 99%